The Relationship Between Body Composition, Physical Activity, Self-Esteem, and Body Image in Female and Male Adolescents - Ligia Rusu; Denisa Piele; Eva Ilie; Gheorghe Ionescu; Mihnea Ion Marin; Mihai Robert Rusu; Mirela Lucia Calina (Sports)
The elements of body composition and their correlation with physical activity, body image, and self-esteem are aspects that require in-depth studies. This link should be seen in the context of the percentage of adipose tissue, which can be modeled via physical activity. The objective of this study is to evaluate the relationships between the parameters that define body composition, self-esteem, body image, and physical activity according to gender. This study included 100 females and 100 males with an average age of 22 years. The evaluation included anthropometric parameters, body composition, self-esteem, physical activity index, and body image perception assessment. The results show that the males exhibited a higher percentage of exceeding the upper limit of normal and average weight; in contrast, there were two times more females exhibiting normal weight than those exceeding the upper limit. Therefore, obesity was higher among males. The average fitness score values were 69.07 for females and 76.53 for males, and the mean fitness was within normal limits. Regarding body image, according to the BSQ, we observed that both groups were not satisfied with and were concerned about their body shape. With respect to the Rosenberg self-esteem scale, the average score for females was 20.27, and for males, it was 19.60; the mean self-esteem value was 66% of the maximum value. In terms of the perceived ideal body size assessed with the Silhouette scale, most of the females were placed at level 3, and the males were placed at level 4. Regarding the physical activity index, females carried out on average 1.5 days of intense physical activity over 7 days, and males were involved in intense physical activity for 2 days. Conclusions: The degree of obesity and therefore the risk of developing cardiovascular disease and metabolic syndrome were higher in males than in females. Although males have a higher degree of obesity, self-esteem is quantified at a higher level of confidence.